Rancang Bangun Aplikasi Pengelolaan Surat Masuk dan Keluar Berbasis Web Pada Dispertan PP Karanganyar - Khusnuliawati, Hardika; Ruswanti, Diyah; Charolina, Astri; Nur’Afnida, Widya (STMIK Banjarbaru, 2024)
Department of Agriculture, Food and Fisheries in Karanganyar Regency is a government agency that still uses a manual process for managing incoming and outgoing mails. This can delay the follow-up of the mail, resulting in a delay in the information delivery process. The aim of this research is to develop a web-based application to make it easier for employees to manage incoming and outgoing mails. This research was carried out using the Waterfall development method, system modeling using Unified Modeling Language (UML) and questionnaire testing using the User Acceptance Test method. The result of this research is to develop a web-based application for managing incoming and outgoing mails which can make it easier for employees in the process of managing data on incoming and outgoing mails, the process of disposition of incoming mails, submission of outgoing mails, reports of incoming and outgoing mails and the data search process. Meanwhile, the results of questionnaire testing using the User Acceptance Test method, obtained a final percentage result of 79%, which means that the level of respondent satisfaction with the application is classified as good.Key Words: Incoming and outgoing mails; Website; Waterfall, Unified Modeling Language; User Acceptance Test;Â AbstrakDinas Pertanian, Pangan dan Perikanan Kabupaten Karanganyar merupakan suatu instansi pemerintahan yang masih menggunakan proses pengelolaan surat masuk dan surat keluar secara manual. Hal tersebut dapat menunda proses tindak lanjut surat, sehingga mengakibatkan keterlambatan proses penyampaian informasi. Tujuan penelitian ini adalah mengembangkan aplikasi berbasis web untuk memudahkan pegawai dalam mengelola data surat masuk dan surat keluar. Penelitian ini dilakukan menggunakan metode pengembangan Waterfall, pemodelan sistem menggunakan Unified Modeling Language (UML) dan pengujian kuesioner menggunakan metode User Acceptance Test. Hasil dari penelitian ini adalah mengembangkan aplikasi pengelolaan surat masuk dan surat keluar berbasis web yang dapat memudahkan pegawai dalam proses pengelolaan data surat masuk dan surat keluar, proses disposisi surat masuk, pengajuan surat keluar, laporan surat masuk dan surat keluar dan proses pencarian data. Sedangkan hasil pengujian kuesioner menggunakan metode User Acceptance Test, didapatkan hasil akhir persentase sebanyak 79%, yang artinya tingkat kepuasan responden terhadap aplikasi terklasifikasi baik.Kata kunci: Surat masuk keluar; Website; Waterfall; Unified Modeling Language; User Acceptance Test;